A green analytical method for the determination of glucosamine using FTIR spectrophotometry - Lodoe Choezom, Ravandur Shivanna Chandan, Gurupadayya Bannimath (Journal of Applied Pharmaceutical Science, 2021)
Glucosamine is an amino sugar, naturally found in cartilage in between the joints. Glucosamine is prescribed for the treatment of osteoarthritis as it may either increase the content of cartilage or inhibit the enzyme responsible for the degradation of cartilage. As per the literature survey, glucosamine was analyzed using different methods, such as High performance liquid chromatography (HPLC) and UV Spectrophotometry, but none was carried out using Fourier Transform Infrared (FTIR) Spectroscopy. Therefore, the present work aims to carry out a green method for the analysis of glucosamine in marketed tablets using FTIR. The qualitative and quantitative analysis of glucosamine was carried out using the KBr pellet method in the mid-infrared region. The method involves the direct measurement of absorbance of the amine group peak at 3309 and 3356 cm−1. The proposed method is validated according to the ICH guidelines (The International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use). Excellent linearity was obtained in the concentration range of 2–7%w/w (R² = 0.9902). The percentage purity of the glucosamine tablet was found to be 99.629%. The results obtained indicate that the proposed method used to analyze glucosamine is precise, accurate, and reproducible. Thus, a simple, rapid, economical, and environmentfriendly method was developed and validated for the analysis of glucosamine in marketed tablets and it can be used for the quality control of routine analysis of this drug.
Keywords: Glucosamine, FTIR, green method, osteoarthritis, validation.